DYNAMICS OF LEARNING MOTIVATION/ DE-MOTIVATION IN THE CONTEXT OF TEACHERS’ COMPETENCIES IN LEARNING MOTIVATION - Anužienė, Birutė; Andriekienė, Rūta Marija; Voropajeva, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article presents findings of the study of students’ attitude toward the dynamics of learning motivation/de-motivation and teachers’ competencies in learning motivation. The study is based on the assumption that students’ motivation in higher education (college or university) is to be supported and enhanced throughout their studies, while positive dynamics of it is subject to the use of learning motivation competencies by teachers in their teaching activities. It is highly important to identify the interrelation between teachers’ competencies in learning motivation and students’ motivation/de-motivation factors so that to establish tools for refining the objects under study, to enable a purposeful action, to make a focused intervention in the ongoing teaching processes for improvement thereof and obtaining better learning outcomes for students. Analysis of students’ attitude might help to respond more comprehensively the following problematic questions: What are motivation/de-motivation factors for student learning? What do teachers’ competencies in learning motivation consist of? In what ways can a teacher support the positive dynamics of learning motivation in students? Thus, this article is aimed to analyse factors for the dynamics of students’ motivation/de-motivation, a content of teachers’ competencies in learning motivation, and their practice from the students’ point of view. The article consists of an introduction and two parts: the first part provides theoretical discourse, the second part is dedicated to an empirical analysis of students’ attitude toward the learning motivation/de-motivation factors, teachers’ competencies in learning motivation, a content thereof, and dynamics of learning motivation. The article ends with a discussion and conclusions, followed by references.